Performance Assessment in Biology Learning: A Study of Implementation in Senior High Schools Implementing the 2013 Curriculum - Mirna Mardianah; Hadi Prasetyo; Djuriah Djuriah; Nellyta Basrie (Journal of Academic Biology and Biology Education, 2024)
Purpose of the study: This study aims to describe the use of performance assessment in biology learning implemented by biology teachers in public senior high schools applying the 2013 Curriculum in South Tangerang. The study specifically seeks to identify teachers’ understanding, assessment practices, and the implementation of performance assessment across learning activities. Methodology: Descriptive research with survey method; questionnaire, interview guide, observation sheet of lesson plans, and documentation analysis; purposive sampling; respondents were six biology teachers from four public senior high schools in South Tangerang; instrument validation through expert judgment; descriptive statistical analysis using percentage calculation and data reduction-display-verification techniques; Microsoft Excel for data tabulation. Main Findings: The findings showed that biology teachers generally understood the basic concept of performance assessment, although understanding of its characteristics was still limited. Observation was dominant for attitude assessment, written tests for knowledge assessment, and performance tasks for skills assessment. Performance assessment had been implemented in biology learning, but its application was not yet fully optimal across all competency domains. Novelty/Originality of this study: This study provides an empirical description of biology teachers’ use of performance assessment within the context of the 2013 Curriculum implementation in South Tangerang public senior high schools. It offers specific evidence on teachers’ understanding, assessment patterns, and implementation challenges, contributing practical insights for improving authentic assessment practices in biology education.